Adversity Quotient pada Pelaku Startup di Yogyakarta: Kegigihan di Tengah Masalah - Akbar Verezha Bintang Ibrahim; Sumaryono Sumaryono (Faculty of Psychology, Universitas Gadjah Mada, 2019)
The purpose of this research was to understand the adversity quotient among startup founders in Yogyakarta. Phenomenology was the approach and analyzed by Miles and Huberman interactive model. The data collection method in this research was a semi-structured interview. Respondents in this study consisted of three startup founders with these criteria: 1) aged 18-24 years old, 2) age of startup at least 1 year, 3) based in Yogyakarta, 4) willing to be interviewed. This study found two forms of adversity quotient on startup founders: 1) coping strategies and 2) characters. Coping strategies encompassed immediate problem solving, having goals and visions, taking lessons from problems, and finding solutions. While the characters consisted of concepts such as responsibility, learning from experience, having strong principles, persistence, and optimism. As a conclusion adversity quotients of startup founders contain two aspects.